PENDAPATAN PETANI PADI SAWAH PENGGUNA PUPUK ORGANIK DAN ANORGANIK DI KABUPATEN OGAN KOMERING ULU (OKU) TIMUR - Hildayanti, Siti Komariah; Mulyana, Andy; Sriati, Sriati; Gofar, Nuni (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
Today eco-friendly rice farming system becomes interesting agribusiness among farmers, traders and regulators. The use of organic fertilizers as one of eco-friendly components in rice farming system is still low. In some rice production center the farmers of organic rice farming system looks higher than non-organic farmers. The question is: is there any difference among farmers whom use organic, semi-organic and inorganic fertilizers statistically? This research aims to know the difference of rice farmer income (organic and inorganic fertilizer) in East Ogan Komering Ulu (EastOKU), South Sumatra. The method used in this research is comparative analysis (independent t-test). The sample farmers are classified into the three clusters. The research shows that the contribution fertilizer cost from semi-organic farming is higher than full organic and inorganic farming. On the other side, t-test result shows that there is no different income among three kinds of using fertilizer.